(untitled) (Research, Society and Development, 2022)
This study aimed to carry out documentary research in secondary databases related to Chagas disease (CD) in the Identity Territory of Irecê, Bahia, Brazil. This is basic research of an exploratory nature. For data collection, an online database was used, such as the Department of Informatics of the Unified Health System (DATASUS) Tablet, Epidemiological Bulletins of the State of Bahia, and documents from the Epidemiological Surveillance of the Government of the State of Bahia. Data were analyzed and presented in the form of tables and graphs. In the study territory, 255 deaths were identified in the Mortality Information System (SIM), of which 67.45% were males and 32.55% were females, both with a prevalent age group of 50 to 59 years. In the Notifiable Diseases Information System (SINAN), a case of acute Chagas disease was reported in the city of Lapão (BA), male aged between 20 and 39 years. In the Hospital Information System of the Unified Health System (SIHSUS), 11 cases of hospital admissions to the SUS for trypanosomiasis were reported in only 4 of the 20 municipalities. Based on the scientific evidence discussed in the work, the transmission of T. cruzi in the territory is mainly done through the vector. This work shows that CD remains a public health problem in Bahia and that there is underreporting about the disease in public health information systems, making possible decision-making by the government and health professionals unfeasible.